2020
DOI: 10.3390/biom10060948
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Properties of Elsholtzia ciliata Essential Oil on Electrical Activity of the Isolated Rabbit Heart and Preferential Inhibition of Sodium Conductance

Abstract: Elsholtzia ciliata essential oil (E. ciliata) has been developed in Lithuania and internationally patented as exerting antiarrhythmic properties. Here we demonstrate the pharmacological effects of this herbal preparation on cardiac electrical activity. We used cardiac surface ECG and a combination of microelectrode and optical mapping techniques to track the action potentials (APs) in the Langendorff-perfused rabbit heart model during atrial/endo-/epi-cardial pacing. Activation time, conduction velocity and AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Our study demonstrates that EO has a potent relaxing influence on smooth muscles in the prostate and aorta which may be related to the inhibition of α 1 -adrenoreceptors. This physiologically relevant effect, together with the previously identified antiarrhythmic and hypotensive effects [1,2], sketches a promising picture of EO's potential therapeutic applications across a diverse spectrum of medical conditions.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our study demonstrates that EO has a potent relaxing influence on smooth muscles in the prostate and aorta which may be related to the inhibition of α 1 -adrenoreceptors. This physiologically relevant effect, together with the previously identified antiarrhythmic and hypotensive effects [1,2], sketches a promising picture of EO's potential therapeutic applications across a diverse spectrum of medical conditions.…”
Section: Discussionmentioning
confidence: 72%
“…Previous electrophysiological studies with Langendorff-perfused rabbit hearts revealed that EO at a higher concentration (0.3 µL/mL) shortened action potentials and slowed the impulse propagation down via the atrioventricular node, inducing an conduction block. These results suggested that EO can have an inhibitory effect not only on Na + -current but also the Ca 2+ -current [2]. Another study found that the furan derivative, 5-hydroxymethylfurfural, relaxed coronary arteries in a concentration-dependent manner and exerted negative inotropic, lusitropic, and chronotropic effects in isolated rat hearts.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The reduction of action potential duration can reduce the occurrence of early depolarization. This experiment provides theoretical basis for E. ciliata in the treatment of arrhythmia [ 48 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%